Analysis for speech and esthetics in sixty consecutive patients with cleft lip and palate - Mahantesh S Shiraganvi; N Kumar; A Desai; TUR Kiran; K Gopalkrishnan (Journal of Oral Biology and Craniofacial Research, 2011)
ABSTRACT: Background: A double-blind retrospective study was carried out at our oral and maxillofacial surgery department to assess speech and esthetics of primary cheiloplasty in patients operated for unilateral complete cleft lip, alveolus and palate. Materials and Methods: Total sample size was 60. All were operated for unilateral complete cleft lip, alveolus and palate. Age range was between 1 and 21 years. Results of surgeries performed by two surgeons were assessed. The speech of all these patients was judged by a single speech therapist who was unaware of the operating surgeon. All patients were assessed for articulatory errors, namely, omission, distortion, substitution, addition and intelligibility. Sixty-eight words in local language (Kannada) were selected by the speech pathologist. All patients were subdivided into three age groups: ≤5 years, 6–10 years and ≥11 years. The cheiloplasty was assessed using VLS (V: vermilion, L: lip, S: scar) scale for vermilion, lip and scar patterns. Results and Conclusion: Patients undergoing palatoplasty in ≤1 year showed good articulation between the age of 5 and 10 years. Articulation and intelligibility was maximum in patients ≥11 years. Patients at this age try various compensatory mechanisms to overcome communication disabilities. Based on the VLS scale, scarring was the least in all patients. Vermilion and lip patterns showed satisfactory results in most of the patients.